1998
DOI: 10.1097/00005537-199806000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Postinflammatory Acquired Atresia of the External Auditory Canal: Treatment and Results of Surgery Over 27 Years

Abstract: Postinflammatory, acquired atresia of the external auditory meatus is a relatively rare consequence of chronic otitis media or recurrent external otitis with an annual incidence of 0.6 cases per 100,000 inhabitants. Primary and late results after operative treatment of this condition in 53 ears over 27 years are presented. Perioperative findings are described, and an outline of applied surgical technique is given. Six patients had bilateral involvement. The male-to-female ratio was 1:2, median age at surgery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 14 publications
4
66
0
7
Order By: Relevance
“…These authors found that the number of ears with a post-operative air-bone gap of less than 20 dB declined from 90 per cent at primary follow up to 61 per cent at 5 years. 12 The present series, smaller in size but representing the longest follow-up period reported to date, found a similar outcome: the proportion of ears benefitting from surgery (i.e. having an air-bone gap of less than 20 dB) progressively declined from 93 per cent to 55 per cent over a mean period of 5 years 5 months.…”
Section: Discussionsupporting
confidence: 70%
“…These authors found that the number of ears with a post-operative air-bone gap of less than 20 dB declined from 90 per cent at primary follow up to 61 per cent at 5 years. 12 The present series, smaller in size but representing the longest follow-up period reported to date, found a similar outcome: the proportion of ears benefitting from surgery (i.e. having an air-bone gap of less than 20 dB) progressively declined from 93 per cent to 55 per cent over a mean period of 5 years 5 months.…”
Section: Discussionsupporting
confidence: 70%
“…Its incidence has been estimated at 0.6 cases per 100,000 [1] . It has different names in literature such as post-inflammatory medial meatal fibrosis [2,3] , post-inflammatory medial canal fibrosis [4] , post-inflammatory acquired atresia [5] , canal atresia [6] , and stenosis of the external auditory canal [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas it is recognized that the incidence of aural atresia is relatively low, with an estimated annual incidence of 0.6 cases per 100,000 inhabitants [26], the estimated number of new cases per year in the United States is 2,000, which is not an insignificant number. It is also likely that veterans with hearing damage resulting from blast injuries will have a significantly higher incidence of acquired aural atresia as a result of damage to the ear and related surgical intervention.…”
Section: Discussionmentioning
confidence: 97%